TBI-QOL: Development and Calibration of Item Banks to Measure Patient Reported Outcomes Following Traumatic Brain Injury. Issue 1 (January 2016) - Tulsky, David S.; Kisala, Pamela A.; Victorson, David; Carlozzi, Noelle; Bushnik, Tamara; Sherer, Mark; Choi, Seung W.; Heinemann, Allen W.; Chiaravalloti, Nancy; Sander, Angelle M.; Englander, Jeffrey; Hanks, Robin; et al.
Abstract : Objective: To use a patient-centered approach or participatory action research design combined with advanced psychometrics to develop a comprehensive patient-reported outcomes (PRO) measurement system specifically for individuals with traumatic brain injury (TBI). This TBI Quality-of-Life (TBI-QOL) measurement system expands the work of other large PRO measurement initiatives, that is, the Patient-Reported Outcomes Measurement Information System and the Neurology Quality-of-Life measurement initiative. Setting: Five TBI Model Systems centers across the United States. Participants: Adults with TBI. Design: Classical and modern test development methodologies were used. Qualitative input was obtained from individuals with TBI, TBI clinicians, and caregivers of individuals with TBI through multiple methods, including focus groups, individual interviews, patient consultation, and cognitive debriefing interviews. Item pools were field tested in a large multisite sample ( n = 675) and calibrated using item response theory methods. Main Outcomes Measures: Twenty-two TBI-QOL item banks/scales. Results: The TBI-QOL consists of 20 independent calibrated item banks and 2 uncalibrated scales that measure physical, emotional, cognitive, and social aspects of health-related quality of life. Conclusions: The TBI-QOL measurement system has potential as a common data element in TBI research and to enhance collection of health-related quality-of-life and PRO data in rehabilitation research and clinical settings. Abstract : Supplemental Digital Content is Available in the Text.